Citrus biotechnology: What has been done to improve disease resistance in such an important crop?. (2019) - Caserta, R.; Teixeira-Silva, N.S.; Granato, L.M.; Dorta, S.O.; Rodrigues, C.M.; Mitre, L.K.; Yochikawa, J.T.H.; Fischer, E.R.; Nascimento, C.A.; Souza-Neto, R.R.; Takita, M.A.; Boscariol-Camargo, R.L.; et al.
Abstract: Citrus cropping is widely distributed as an important economic activity worldwide. Amongst the major producers are Brazil, China, United States, Mexico and some European countries. Brazil is the largest sweet orange producer accounting for more than three-quarters of the orange juice exports around the world, followed by China and the United States (Foreign Agricultural Service/USDA, 2019). Although juice is the main commodity in many countries producing citrus, by-products like essential oils, molasses, dried pulp, pectin, blend syrup and others are also part of the citrus trade chain. Since citriculture is threatened by several pathogens and its control is mainly based on regular chemical applications both during plant development and post-harvest, management becomes a non-environmentally friendly strategy. Meanwhile, consumers are searching for sustainable products of great quality and high aggregated value pressuring the agricultural industry to crop in a sustainable manner. In this scenario, citriculture also needs innovative solutions to meet such demand. Although classic breeding programs succeeded over time, citrus narrow genetic base and long evaluation periods turns it difficult to demand faster solutions for emerging problems. Biotechnology rises as a source of innovative solutions since new varieties can be developed for specific problems. In this context, the use of biotechnology approaches involving genetic engineering that allow the development of more resistant varieties are the focus of many research groups. Here we show how biotechnology has been used to develop citrus plants more resistant to the main phytopathogens that impact citrus production.